2008
DOI: 10.1016/j.juro.2008.04.018
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the 2005 International Society of Urological Pathology Consensus Conference on Standard Gleason Grading of Prostatic Carcinoma in Needle Biopsies

Abstract: The findings of this study indicate that the recommendations of the International Society of Urological Pathology are a valuable refinement of the standard Gleason grading system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 14 publications
5
92
1
5
Order By: Relevance
“…The International Society of Urological Pathology Consensus Conference modified the Gleason grading in 2005 (Shah et al, 2009) according to which Gleason grades were updated according to new criteria. Several studies have validated the prognostic value of these modifications (Billis et al, 2008;Dong et al, 2012). As shown in Table (5), Gleason score 7 was the commonest score in our series, followed by Gleason score 9.…”
Section: Discussionsupporting
confidence: 54%
“…The International Society of Urological Pathology Consensus Conference modified the Gleason grading in 2005 (Shah et al, 2009) according to which Gleason grades were updated according to new criteria. Several studies have validated the prognostic value of these modifications (Billis et al, 2008;Dong et al, 2012). As shown in Table (5), Gleason score 7 was the commonest score in our series, followed by Gleason score 9.…”
Section: Discussionsupporting
confidence: 54%
“…After the re-evaluation, a higher number of patients was assigned to the prognostic group of GS 8-10, exhibiting, at follow-up, a shorter time to biochemical disease recurrence (log-rank P=0.011) (9).…”
Section: Introductionmentioning
confidence: 99%
“…Helpap and Egevad 9 compared the grade distributions in needle biopsies for the 2 grading systems and found that the proportion of cancers with a score of 7 increased from 26% in the classic system to 68% in the ISUP 2005 modified Gleason scoring system; the proportion of cancers with a score of 6 decreased from 48% to 22%. In a similar investigation, Billis and colleagues 10 found that the proportion of cancers with a score of 7 increased from 26% in the classic system to 39% in the ISUP 2005 modified Gleason scoring system; the proportion of cancers with a score of 6 decreased from 68% to 39%. In another study, 11 the ISUP 2005 modified Gleason scoring system resulted in needle biopsy scores that were higher than the scores of the classic system by 16%.…”
Section: Commentmentioning
confidence: 86%